2020
DOI: 10.3390/ijerph17031041
|View full text |Cite
|
Sign up to set email alerts
|

Active Commuting and Depression Symptoms in Adults: A Systematic Review

Abstract: Physical activity (PA) is suggested to have a protective effect against depression. One way of engaging in PA is through active commuting. This review summarises the literature regarding the relationship between active commuting and depression among adults and older adults. A systematic review of studies published up to December 2019, performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, was conducted using three databases (PubMed, Scopus, and Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
0
14
0
4
Order By: Relevance
“…Exercise is planned, structured physical activity with the objective of improving or maintaining physical fitness ( Caspersen et al, 1985 ). Recent studies suggested that engaging in exercise training might be even more effective than simply being physically active: According to a recent systematic review, only two of seven studies reported a positive association between switching to an active commute to the workplace and a reduction of depressive symptoms ( Marques et al, 2020 ). In comparison, aerobic exercise that focuses on cardiovascular fitness has large positive effects on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is planned, structured physical activity with the objective of improving or maintaining physical fitness ( Caspersen et al, 1985 ). Recent studies suggested that engaging in exercise training might be even more effective than simply being physically active: According to a recent systematic review, only two of seven studies reported a positive association between switching to an active commute to the workplace and a reduction of depressive symptoms ( Marques et al, 2020 ). In comparison, aerobic exercise that focuses on cardiovascular fitness has large positive effects on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…On this point, as an important source of PA [11], active school travel (AST) may be a way against depressive symptoms. There is evidence concerning the relationship of AST with depressive symptoms among adults [12]. As a result, it is assumed and expected that AST may play a role in preventing depressive symptoms among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…33 Cycling for transportation may also have important mental health benefits. Some studies have demonstrated a decrease in depression symptoms, 34,35 while others have demonstrated an overall increase in emotional well-being and happiness. 36,37 Cycling as active transportation has shown to have indirect benefits for health.…”
Section: Editor's Key Pointsmentioning
confidence: 99%